Islamic Art: An Analytical Study of Ismail Al-Faruqi’s Views - ALASHARI, DUAA (The journal of contemporary issues in business and government, 2021)
Ismail Al Faruqi offered many opinions on the principles and foundations of the aesthetic of Islamic art. For this reason, this paper aims to present an analytical study on the set of opinions presented by Al-Faruqi to enrich Islamic art, and also to reveal some concepts related to the beauty of Islamic art from Al-Faruqi's point of view. The approach followed in this study is the methodology of content analysis. The study concluded that Ismail Al-Faruqi is the founder of the Islamic aesthetic and artistic theory, based on the Holy Quran as the first source of Islamic knowledge. The study also concluded that monotheism (Tawhid) is the principle of beauty inherent in Islamic art, based on the opinion of Al-Faruqi.